Synthesis and Antimicrobial Activity of 1,2,4-Triazoles - R. U. Roy; A. R. R. Desai; K. R. Desai (E-Journal of Chemistry)
Several 3-(4'-nitrophenyl)-4-(4"-chloro benzamido)-5-substituted phenyl)-4H-1,2,4-triazole (3a-3e) and 3-(4'-nitrophenyl)-4-(4"-methyl benzenesulphonamido)-5-substituted phenyl)-4H-1,2,4-triazole (4a-4e) have been synthesised. Representative compounds were screened for antibacterial, antifungal activity. Most of them showed significant antibacterial activity.